Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2196/jmir.3322
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Virtual Patient Simulation With Mannequin-Based Simulation for Improving Clinical Performances in Assessing and Managing Clinical Deterioration: Randomized Controlled Trial

Abstract: BackgroundVirtual patient simulation has grown substantially in health care education. A virtual patient simulation was developed as a refresher training course to reinforce nursing clinical performance in assessing and managing deteriorating patients.ObjectiveThe objective of this study was to describe the development of the virtual patient simulation and evaluate its efficacy, by comparing with a conventional mannequin-based simulation, for improving the nursing students’ performances in assessing and managi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(138 citation statements)
references
References 28 publications
3
127
1
7
Order By: Relevance
“…(). Six countries were represented across the reviewed studies with the greater numbers conducted in the United States ( n = 3), (Lindsey & Jenkins, ; Ozekcin, Tuite, Willner, & Hravnak, ; Rose, Hanna, Nur, & Johnson, ), Singapore ( n = 2) (Liaw, Chan, Chen, Hooi, & Siau, ; Liaw, Wong, Ang, et al., ; Liaw, Wong, Chan, et al., ), in hospitals ( n = 7) (Cahill et al., ; Kyriacos, Jelsma, James, & Jordan, ; Ludikhuize, De Jonge, & Goossens, ; Merriel et al., ; Ozekcin et al., ; Rose et al., ; Shaddel, Khosla, & Banerjee, ) and simulation settings ( n = 3) (Liaw, Wong, Ang, et al., ; Liaw, Wong, Chan, et al., ; Lindsey & Jenkins, ). Sample size varied between 19 (Shaddel et al., ) and 147 (Cahill et al., ) participants.…”
Section: Resultsmentioning
confidence: 99%
“…(). Six countries were represented across the reviewed studies with the greater numbers conducted in the United States ( n = 3), (Lindsey & Jenkins, ; Ozekcin, Tuite, Willner, & Hravnak, ; Rose, Hanna, Nur, & Johnson, ), Singapore ( n = 2) (Liaw, Chan, Chen, Hooi, & Siau, ; Liaw, Wong, Ang, et al., ; Liaw, Wong, Chan, et al., ), in hospitals ( n = 7) (Cahill et al., ; Kyriacos, Jelsma, James, & Jordan, ; Ludikhuize, De Jonge, & Goossens, ; Merriel et al., ; Ozekcin et al., ; Rose et al., ; Shaddel, Khosla, & Banerjee, ) and simulation settings ( n = 3) (Liaw, Wong, Ang, et al., ; Liaw, Wong, Chan, et al., ; Lindsey & Jenkins, ). Sample size varied between 19 (Shaddel et al., ) and 147 (Cahill et al., ) participants.…”
Section: Resultsmentioning
confidence: 99%
“…Outra consideração que favorece o uso desse tipo de simulação é o tempo do corpo docente, a disponibilidade de instalações e problemas com agendamentos nos laboratórios (20) . As simulações baseadas em manequim envolvem um pequeno número de alunos de uma só vez.…”
Section: Discussionunclassified
“…As simulações baseadas em manequim envolvem um pequeno número de alunos de uma só vez. Além disso, uma quantidade considerável de tempo de faculdade é necessária para realizar sessões repetidas (20) . Tanto a simulação com paciente virtual quanto a simulação baseada em manequim são estratégias eficazes de aprendizagem para melhorar o desempenho clínico dos estudantes de enfermagem (20) .…”
Section: Discussionunclassified
“…Although previous studies have also shown the effectiveness of using simulation in training for acute care,35 36 the availability of simulation facilities and logical issues of scheduling the learners and facilitators remain a major challenge,18 40 especially for institutions where large groups of learners are required to be trained. Computer systems now allow the incorporation of a variety of instructional activities that provide active learning.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown this strategy to be at least as good as, if not better than, the mannequin-based simulation 18. An interactive web-based educational programme was therefore developed for hospital nurses to enhance their competencies in acute nursing care 19.…”
Section: Introductionmentioning
confidence: 99%